Design-Centered Professional Development for Digital, Outcome-Aligned Classroom Assessment in Tomohon Primary Schools - Feibry Feronika Wiwenly Senduk (CV. TOTUS TUUS, 2025)
The global shift toward competency-based education underscores the need for authentic, transparent assessment, yet teacher readiness to enact such practices remains uneven in Indonesian primary schools implementing the Merdeka Curriculum. To address this gap, we aimed to strengthen teachers’ capacity to design digital, outcome-aligned evaluations—combining LKPD/task sheets with clear analytic rubrics—and to document resulting changes in classroom practice. Twenty-eight Tomohon primary teachers participated in a practice-proximal workshop followed by mentoring, with data drawn from pre–post rubric-based competency scores across five domains, audits of Canva-produced artifacts, brief classroom pilot logs, and surveys of self-efficacy and intention to use. Results showed significant median improvements in all domains, with the largest gains in rubric structure and constructive alignment; by program’s end, 92.9% of participants produced complete digital evaluation packs and 71.4% advanced beyond static layouts to interactive or workflow-integrated use. Classroom pilots indicated high on-task behavior and more frequent student reference to success criteria, while teachers reported higher self-efficacy and strong intentions for sustained adoption. These findings suggest that design-centered professional development, paired with low-barrier authoring tools, can accelerate authentic assessment capacity and enhance classroom processes in resource-varied primary settings. Benefits to schools include a shared language of quality, faster planning-to-practice cycles, and clearer, fairer evaluations for learners and families. We recommend scaling bimtek-plus-mentoring with rubric libraries, embedding brief accessibility micro-clinics, formalizing peer moderation, and extending future cycles to feedback quality and inclusive/multimodal rubrics.